INVESTIGATIONS OF CONVERGENCE OF METHODS OF DECOMPOSITION - Шувар, Богдан Антонович; Копач, Михайло Іванович; Обшта, Анатолій Феліксович; Наконечна, Ганна Володимирівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Some sufficient conditions of convergence of a class of methods of decomposition for linear equations with bounded operators are established. These condition does not require neiser fixed sign of the operator or bounds for the operator spectral radius.